2017
DOI: 10.1016/j.biocel.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell neoplasia in situ: The precursor cell for invasive germ cell tumors of the testis

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. AbstractGerm cell neoplasia in situ is the non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…The reason for this contrast may partly be due to the localization of the tumor within the testis. Typically, the developed GCNIS is found above the basement membrane in seminiferous tubules, which are located in the intratesticular environment and therefore separate from the bloodstream via the blood testis barrier (BTB) (49,50). The BTB's primary function is to prevent both antibodies and T lymphocytes from affecting the testis (51).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this contrast may partly be due to the localization of the tumor within the testis. Typically, the developed GCNIS is found above the basement membrane in seminiferous tubules, which are located in the intratesticular environment and therefore separate from the bloodstream via the blood testis barrier (BTB) (49,50). The BTB's primary function is to prevent both antibodies and T lymphocytes from affecting the testis (51).…”
Section: Discussionmentioning
confidence: 99%
“…These are usually manifested by antenatal origin. Undescended testis and hypospadias give symptoms at neonatal period whereas poor quality of semen and development of TGCT manifest after puberty (9). Animal models and epidemiological researches have revealed that deficiencies in the production of androgens, disorders of androgen receptor expression, disturbance in androgen levels, exposure to anti-androgenic or estrogenic disruptors were attributed to the pathogenesis of TDS (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more evidence is needed to reinforce TDS hypothesis (8). According to the literature, semen analysis and testicular histology support the association between TGCT and TDS (9). But there is no detailed evaluation to show the effects of TDS components on TGCT prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…These cancers are clinically and histologically classified into two variants, being seminoma (SE) and nonseminoma (NS). Both arise from a common cancer stem cell, currently referred to as Germ Cell Neoplasia In Situ (GCNIS) 2,3 , which resembles totipotent primordial germ cells (PGC) / gonocytes. Patients with proven GCNIS have a 70% chance of progression to TGCC (both SE and NS) within 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…About 50% of the TGCC patients present with a NS, that can be composed of different histological elements, embryonal carcinoma (EC), teratoma (TE), yolk sac tumor (YST), and choriocarcinoma (ChC), either pure or mixed. The EC is the pluripotent stem cell component of NS, which can mimic normal early embryogenesis including the formation of so called embryonal bodies (EB), and thereby give rise to all differentiated components [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%